2017
DOI: 10.1080/19425120.2017.1290722
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Spawning Dynamics of Southern Flounder in the North‐Central Gulf of Mexico

Abstract: Southern Flounder Paralichthys lethostigma is the most commonly harvested flatfish in the north‐central Gulf of Mexico (GOM), yet knowledge of this species’ growth and reproduction is limited for the Mississippi region. Given the offshore spawning migrations and likely mixing between state‐managed units of the GOM Southern Flounder stock, small‐scale environmental influences may constitute a major driver of life history dynamics during early life residency in nearshore estuaries. Therefore, estimates of local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…We found that although the relationship between GSI and GFBW in Red Drum was significant, it explained very little of the variance (10% for female‐specific values; 18% for male‐specific values), indicating that GSI is a good indicator of spawning preparedness (Corey et al. ). The significant relationship was likely attributable to the number of young (age < 5) individuals that were histologically identified as mature but had very low GSI values.…”
Section: Discussionmentioning
confidence: 99%
“…We found that although the relationship between GSI and GFBW in Red Drum was significant, it explained very little of the variance (10% for female‐specific values; 18% for male‐specific values), indicating that GSI is a good indicator of spawning preparedness (Corey et al. ). The significant relationship was likely attributable to the number of young (age < 5) individuals that were histologically identified as mature but had very low GSI values.…”
Section: Discussionmentioning
confidence: 99%
“…For the recent time series, the lack of correlation with neighboring estuaries and curious occurrence of correlation with furthest distance estuaries again indicates the lack of a regional pattern to this synchrony. The absence of a relationship with neighboring estuaries could be explained by the life history of southern flounder, a relatively short‐lived fish that matures by age‐1 or age‐2 (Corey, 2016; Midway & Scharf, 2012), as faster life history species (early reproduction, shorter generation time, short longevity) exhibit less spatial synchrony than slower life history species (Marquez et al, 2019). The lack of local scale spatial synchrony, combined with the evidence for a range‐wide decline, is concerning as increased synchrony among interacting spatial populations can reduce the resilience of declining stocks (Koenig & Liebhold, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Southern flounder ( Paralichthys lethostigma ) are distributed in the southeastern United States, with populations in the Gulf of Mexico and along the Atlantic coast in North Carolina (NC), near the northern edge of the species range. Adult flounder are batch spawners that migrate out from estuaries to coastal waters to spawn during late fall to early winter 23 . The fertilized eggs are buoyant and will float for two to three days until hatching.…”
Section: Introductionmentioning
confidence: 99%